Politecnia e polivalência na organização do trabalho em cooperativas populares e tradicionais - Chiariello, Caio Luis (Universidade Federal de São Carlos, 2012)
This PhD thesis contains the theoretical and empirical approach about the work organization on popular and traditional cooperatives in Brazil, presenting the concepts of polytechni and polyvalence within the recent changes in the work scenario. The concept of polyvalence is related to flexible production models, providing greater workers participation in formulation and execution of different tasks. Polyvalent workers have many skills and assume responsibilities, but although polyvalence points to a greater convergence between intellectual and manual labor, it doesn t overcome the gap between execution and management, promoting only the enrichment and expansion of tasks, not questioning capital domination over labor. Therefore, the concept of polytechni proposes an omnilateral worker, refusing the labor technical division under capitalism and arguing that workers might participate fully in the conduction of work process. The incorporation of the knowledge about scientific and technical activities by omnilateral workers approaches 'hand and brain' and inhibits the separation between who manage and who execute the work. Thus, polytechni gives rise to self-management conducted by workers, based on genuine cooperation, searching for the transformation of society in economic, political and social dimensions. The Thesis presents an empirical study in a traditional cooperative - COCAMAR - linked to the agribusiness and applying the polyvalence in their work organization, and four popular cooperatives - COOPAN; COOPERUNIÃO; COPAVI and COPAVA linked to social movements and agrarian reformand and seeking to adhere to the polytechnic principles the selfmanagement. The discussion about the work organization trajectory of the five cooperatives, their internal democracy and power relations, dynamics between management and execution, job rotation and work activities, the working journey, paymente and control and education for the work presents the singularities, approaches and contradictions over the organization of work in these cooperative.
Keywords: Cooperativismo; Organização do trabalho; Politecnia; Polivalência; Economia solidária; Cooperativism; Work organization; Polytechni; Polyvalence; ENGENHARIAS::ENGENHARIA DE PRODUCAO